Apartment Rental Market in Border Cities of Poland and Ukraine - Hełdak, Maria; Kucher, Lesia (Geomatics and Environmental Engineering, 2024)
This article is a contribution to the research that addresses the levels of apartment rental costs in Poland and Ukraine. The city of Rzeszów in Poland and Lviv in Ukraine – voivodeship capital cities that are located about 100 km from the Polish-Ukrainian border – were selected for the analysis. The purpose of the research is to compare the rental costs of apartments and to determine the correlation between the average rental rate and location of an apartment in the city as well as its floor, area, and residential standard. The experimental part of the article presents research results based on analyzing more than 300 apartment rental offers in the Rzeszów and Lviv housing market at the turn of 2022–2023. The possibility of renting an apartment results from the financial capacity of potential tenants, which is unavailable to people with low incomes; hence, the study also analyzed market rental rates in the context of the minimum wage in Poland and Ukraine in 2022.